Beyond the Black Study Abroad Experience: Developing the Young AfricanA Leadership Initiative at Howard University (International Journal of Multidisciplinary Perspectives in Higher Education, 2019)
The lack of participation in study abroad programs by Black students is a persistent concern in international higher education. The Penn Center for Minority Serving Institutions (Gasmen, 2016), reported three main obstacles facing students of color: financial burdens, fear of anticipated racism, and finding study abroad programs of interest to them. While most scholarship on Black students studying abroad concentrates solely on increasing the number of opportunities, this article was determined to shift the focus onto the cultural gap. This paper describes the development of the 2014 Young African Leadership Initiative (YAALI) fellowship that aims to go beyond the typical study abroad experience for Black students by providing travel opportunities to Africa, combatting fear with education and mapping a collective self-reflective experience. Over 4 years of the YAALI fellowship successfully increased Black students’ participation in study abroad experiences.